Identifying childhood leukemia with an excess of hematological malignancies in first-degree relatives in Brazil - Mendes-de-Almeida, Daniela P.; Andrade, Francianne G.; Sampaio Carvalho, Maria do Perpétuo Socorro; Córdoba, José Carlos; Souza, Marcelo dos Santos; Neto, Paulo Chagas; Spector, Logan G.; Pombo-de-Oliveira, Maria S. (Frontiers in Oncology, 2023)
Background Familial aggregation in childhood leukemia is associated with epidemiological and genomic factors. Albeit epidemiological studies on the familial history of hematological malignancies (FHHM) are scarce, genome-wide studies have identified inherited gene variants associated with leukemia risk. We revisited a dataset of acute lymphoblastic leukemia (ALL) and acute myeloid leukemia (AML) patients to explore the familial aggregation of malignancies among their relatives. Methods A series of 5,878 childhood leukemia (≤21 years of age) from the EMiLI study (2000-2019) was assessed. Lack of well-documented familial history of cancer (FHC) and 670 cases associated with genetic phenotypic syndromes were excluded. Leukemia subtypes were established according to WHO recommendations. Logistic regression-derived odds ratios (OR), and 95% confidence intervals (CI) were performed and adjusted by age as a continuous variable, where ALL was the reference group for AML and conversely. The pedigree of 18 families with excess hematological malignancy was constructed. Results FHC were identified in 472 of 3,618 eligible cases (13%). Ninety-six of the 472 patients (20.3%) had an occurrence of FHHM amongst relatives. FHC was significantly associated with AML (OR, 1.36, 95% CI,1.01-1.82; p=0.040). Considering only first-degree relatives, the OR was 2.92, 95% CI,1.57-5.42, and adjOR, 1.16 (1.03-1.30; p=0.012) were observed. Conclusions Our findings confirmed that AML subtypes presented a significant association with hematological malignancies in first-degree relatives. Genomic studies are needed to identify germline mutations that significantly increase Brazil's risk of developing myeloid malignancies.